Risk-off shocks and spillovers in safe havens - John Beirne; Eric Sugandi (Asian Development Bank Institute (ADBI), 2022)
This paper examines real and financial spillovers to safe haven financial flow destinations due to risk-off shocks in global financial markets. Using country-specific structural vector autoregression (VAR) models over the period 1990 to 2021, we show that dynamics for Japan appear to be different to those of Switzerland and the US in four main ways. First, in response to risk-off episodes over the estimation period, the yen real effective exchange rate (REER) appreciates sharply and significantly, with the effect persisting over time. Second, no significant effects on portfolio flows to Japan are found, in spite of the exchange rate effects, suggesting a rapid adjustment of financial markets to shifts in equilibrium exchange rates. Third, negative real spillovers from risk-off shocks appear to only apply to Japan with exchange rate appreciation exacerbating declines in GDP growth. Fourth, risk-off shocks do not have a statistically significant effect on domestic economic policy uncertainty in Japan, which may be related to the strong expectations priced in of overseas portfolio holdings repatriated back to Japan. Our findings have important implications for policymakers in safe haven destinations in managing domestic financial vulnerabilities associated with risk-off episodes.
Keywords: F32; F41; F62; 330; risk-off episodes; safe haven assets; economic policy uncertainty